Analisis Nilai Pendidikan Tauhid Dalam Kitab Tanqih Al-Qaul Al-Hatsits Fi Syarh Lubab Al-Hadits Karya Syekh Imam Nawawi Al-Jawi Al-Bantani Dan Aktualisasinya Pada Konteks Pendidikan Islam Modern - Wildan Maulana Alkirom; Muhammad Fodhil (Educational Research Center, 2026)
Tauhid constitutes the fundamental foundation of Islamic education, serving to shape students’ faith orientation, attitudes, and behavior. However, in modern educational practice, the internalization of tawhid values has often not been integrated in a comprehensive and contextual manner. This study aims to analyze the educational values of tawhid contained in the book Tanqih al-Qaul al-Hatsits fi Syarh Lubab al-Hadits by Shaykh Imam Nawawi al-Jawi al-Bantani and to examine their actualization within the context of modern Islamic education. This research employs a qualitative approach with library research as its method. The object of the study is the text of Tanqih al-Qaul al-Hatsits, with data collected through document analysis, while data analysis is conducted using descriptive-interpretative content analysis. The findings indicate that the book contains tawhid educational values encompassing faith in Allah’s asmā’ wa ṣifāt, belief in qaḍā’ and qadar, the attitude of tawakkul, and conviction in the wisdom of divine decrees, all of which contribute to the formation of moral awareness, spiritual resilience, and mature attitudes. The actualization of these values in modern Islamic education can be realized through the integration of tawhid into the curriculum, learning processes, and student character development. This study concludes that the tawhid educational values contained in the book are relevant and significant as a foundation for developing holistic and transformative Islamic education.